Strategi Inovatif Pendampingan Guru PKBM melalui Integrasi Budaya Lokal dan Media Digital Interaktif: Innovative Strategies for PKBM Teachers: Integrating Local Culture and Interactive Digital Media - Ratnawati, Oktaviana Ainun; Rizaldi, Muhammad; Purtina, Arna; Damayanti, Irma; Artika, Zahra Dwi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The advancement of educational technology has opened new opportunities to strengthen the implementation of Project-Based Learning (PjBL). Three training sessions were conducted as part of the mentoring program. The first training aimed to equip PKBM teachers with proficiency in SketchUp. The second training focused on developing teachers' skills in utilizing Evobook. The third training was designed to equip teachers with the ability to create miniature models of Huma Betang. Based on participants' post-training questionnaires, the average improvement in understanding of SketchUp and Evobook was 4.56. The highest score in this aspect was achieved by PKBM Homy School (4.80), while the lowest was Candra Kirana (4.44). The ease of use of both media was rated at 4.13, with Homy School (4.30) receiving the highest score and Bangkirai (4.00) the lowest. In terms of usefulness for learning, the average rating was 4.56, with Homy School (4.90) scoring the highest and Candra Kirana (4.13) the lowest. The relevance of SketchUp and Evobook to participants' needs received an average score of 4.36, with Homy School (4.70) at the highest and Candra Kirana (4.06) at the lowest. Meanwhile, participants' interest in applying these tools in their classrooms averaged 4.49, with Homy School (4.70) the highest and Candra Kirana (4.31) the lowest.